008 ARC Genotype Modulates Slow Wave Sleep Following Total Sleep Deprivation. (3rd May 2021) - Satterfield, Brieann; Lawrence-Sidebottom, Darian; Schmidt, Michelle; Wisor, Jonathan; Van Dongen, Hans
Abstract: Introduction: The activity-regulated cytoskeleton associated protein (ARC) gene is an immediate early gene that is involved in synaptic plasticity. Recent evidence from a rodent model suggests that Arc may also be involved in sleep homeostasis. However, little is known about the molecular mechanisms regulating the sleep homeostat. In humans, sleep homeostasis is manifested by a marked increase in slow wave sleep (SWS) following acute total sleep deprivation (TSD). There are large, trait individual differences in the magnitude of this SWS rebound effect. We sought to determine whether a single nucleotide polymorphism (SNP) of the ARC gene is associated with individual differences in SWS rebound following TSD. Methods: 64 healthy normal sleepers (ages 27.2 ± 4.8y; 32 females) participated in one of two in-laboratory TSD studies. In each study, subjects had a baseline day with 10h sleep opportunity (TIB 22:00–08:00) which was followed by 38h TSD. The studies concluded with 10h recovery sleep opportunity (TIB 22:00–08:00). Baseline and recovery sleep were recorded polysomnographically and scored visually by a trained technician. Genomic DNA was extracted from whole blood. The ARC c.*742 + 58C>T non-coding SNP, rs35900184, was assayed using real-time PCR. Heterozygotes and T/T homozygotes were combined for analysis. The genotype effect on time in SWS was assessed using mixed-effects ANOVA with fixed effects for ARC genotype (C/C vs. T carriers), night (baseline vs. recovery), and their interaction, controlling for study. Results: The genotype distribution in this sample – C/C: 41; C/T: 17; T/T: 6 – did not vary significantly from Hardy-Weinberg equilibrium. There was a significant interaction between ARC genotype and night (F1, 62=7.27, p=0.009). Following TSD, T allele carriers exhibited 47.6min more SWS compared to baseline, whereas C/C homozygotes exhibited 62.3min more SWS compared to baseline. There was no significant difference in SWS between genotypes at baseline (F1, 61=0.69, p=0.41). Conclusion: ARC T allele carriers exhibited an attenuated SWS rebound following TSD compared to those homozygous for the C allele. This suggests that the ARC SNP is associated with trait individual differences related to sleep homeostasis, and may thus influence molecular mechanisms involved in long-term memory. Support (if any): ONR N00014-13-1-0302, NIH R21CA167691, and USAMRDC W81XWH-18-1-0100.